Indigenous Homelands and Environmental Assimilation: Canada’s Impact Assessment Act (2019), and the Public Interest Determination - Tsuji, Stephen (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2026)
Canada’s Impact Assessment Act (2019) presents threats to Indigenous homelands through environmental assimilation and the national public interest. The “taken-up” clause in the numbered treaties, unilateral exemption stipulation for designated projects, and other discretionary decision-making powers in the Impact Assessment Act all override sections in these documents or other pieces of legislation safeguarding Indigenous homelands, their way of life, and their rights—inherent and treaty. This research focuses on the views of Canada’s Indigenous Peoples on how the Impact Assessment Act (2019) and other historical agreements and legislation have and will affect their homelands, way of life, and wellbeing.